Architectures of Portable Systems for Orientation of the Blind - Аврунін, О. Г.; Соколов, А. А.; Соколов, А. М. (My University, 2022)
This paper analyzes the differences and disadvantages of various electronic assistants for the blind. It also describes our architecture.
Keywords: blind; tactile feedback; electronic assistant; parallax